Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.joc.2c02179
|View full text |Cite
|
Sign up to set email alerts
|

Advancements and Challenges in Reductive Conversion of Carbon Dioxide via Thermo-/Photocatalysis

Abstract: Carbon dioxide (CO2) is the major greenhouse gas and also an abundant and renewable carbon resource. Therefore, its chemical conversion and utilization are of great attraction for sustainable development. Especially, reductive conversion of CO2 with energy input has become a current hotspot due to its ability to access fuels and various important chemicals. Nowadays, the controllable CO2 hydrogenation to formic acid and alcohols using sustainable H2 resources has been regarded as an appealing solution to hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 176 publications
0
12
0
1
Order By: Relevance
“…Thus, this study might open new opportunities in the design of more effective cocatalysts (inorganic catalysts, [76][77][78][79] MOFs, 80 covalent organic frameworks, 81,82 phthalocyanine derivatives and so on), which could physically or chemically combine with other semiconductor photocatalysts to achieve outstanding performance for extensive applications. 83,84…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study might open new opportunities in the design of more effective cocatalysts (inorganic catalysts, [76][77][78][79] MOFs, 80 covalent organic frameworks, 81,82 phthalocyanine derivatives and so on), which could physically or chemically combine with other semiconductor photocatalysts to achieve outstanding performance for extensive applications. 83,84…”
Section: Discussionmentioning
confidence: 99%
“…Reductive CO 2 transformation implies a decrease in the CO 2 oxidation state and has gained sustained attention due to its ability to access fuels and various important chemicals, among which the reductive functionalization of CO 2 , i.e., CO 2 reduction accompanied by new C–X bond formation, breaks through the limitation of the CO 2 valence state; therefore, CO 2 can be used as a methylation, methylenation, or formylation reagent for a suitable nucleophile. , …”
Section: Thermocatalytic Co2 Conversionmentioning
confidence: 99%
“…Reductive CO 2 transformation implies a decrease in the CO 2 oxidation state and has gained sustained attention due to its ability to access fuels and various important chemicals, among which the reductive functionalization of CO 2 , i.e., CO 2 reduction accompanied by new C−X bond formation, breaks through the limitation of the CO 2 valence state; therefore, CO 2 can be used as a methylation, methylenation, or formylation reagent for a suitable nucleophile. 27,28 Our group concentrates on catalyst development and product regulation for the reductive functionalization of CO 2 with amine using hydrosilane as a reductant. It is found that the slightly polar Si−H bond in hydrosilanes can be activated by silicophilic species such as the carboxylate anion by forming a hypervalent silicon intermediate.…”
Section: Reductive Transformation Of Comentioning
confidence: 99%
“…In the last three decades, numerous research efforts have been made to develop active heterogeneous catalysts for the conversion of CO 2 by three processes to produce methanol. A large number of review articles, publications, and books ,,, have been published on research topics of CO 2 conversion such as CO 2 utilization by thermal catalysis, , electrocatalytic reduction, , photocatalytic synthesis, ,, plasma, and other methods. Recently, the research group of Shanmuga and Ramyashree published a review article on MOF compounds for PCCR of methanol . In 2022, Gawande’s group discussed recent developments in the photocatalytic hydrogenation of CO 2 to methanol.…”
Section: Introductionmentioning
confidence: 99%